Post-concussive symptoms mediate the relationship between sleep problems and participation restrictions among veterans with mild traumatic brain injury - Kinney, Adam R.; Yan, Xiang-Dong; Schneider, Alexandra L.; King, Samuel; Forster, Jeri E.; Bahraini, Nazanin; Brenner, Lisa A. (Frontiers in Rehabilitation Sciences, 2022)
Background: Sleep problems are common among Veterans with mild traumatic brain injury (mTBI) and may contribute to participation restrictions. However, little is known regarding explanatory mechanisms underlying this relationship. Sleep problems are associated with post-concussive symptoms (e.g., headaches). In turn, post-concussive symptoms contribute to participation restrictions. We hypothesized that post-concussive symptom severity mediates the purported relationship between sleep problems and participation restrictions among Veterans with mTBI. Materials and Methods: This study was a retrospective analysis of clinical data among Veterans with mTBI receiving Veterans Health Administration outpatient care. Sleep problems (yes/no) were identified using the sleep-related item from the Neurobehavioral Symptom Inventory (NSI). Post-concussive symptoms were measured using remaining NSI items. Participation restrictions were measured using the Mayo-Portland Adaptability Inventory Participation Index. We specified a latent variable path model to estimate relationships between: 1) sleep problems and three latent indicators of post-concussive symptoms (vestibular-sensory [e.g., headache]); mood-behavioral [e.g., anxiety]; cognitive [e.g., forgetfulness]); and, 2) the three latent indicators of post-concussive symptoms and two latent indicators of participation restrictions (social and community participation [e.g., leisure activities]; productivity [e.g., financial management]). We examined the indirect effects of sleep problems upon participation restrictions, as mediated by post-concussive symptoms. All estimates were adjusted for sociodemographic factors (e.g., age), injury characteristics (e.g., blast), and co-morbid health conditions (e.g., depression). Results: 87% reported sleep problems. Sleep problems were associated with greater restrictions in social and community participation, as mediated by mood-behavioral (β = 0.41, p < .001) and cognitive symptoms (β = 0.13, p < .001). There was no evidence that vestibular-sensory symptoms mediated this relationship (β = -0.01, p = .48). Sleep problems were associated with greater productivity restrictions, as mediated by vestibular-sensory (β = 0.16, p < .001) and cognitive symptoms (β = 0.14, p < .001). There was no evidence that mood-behavioral symptoms mediated this relationship (β = 0.02, p = .37). Discussion: Findings suggest that evidence-based sleep treatment should occupy a prominent role in rehabilitation of Veterans with mTBI. Indirect effects of sleep problems were conditional on the specific nature of participation, informing individualized rehabilitative care for Veterans with mTBI.